1982
DOI: 10.1149/1.2123830
|View full text |Cite
|
Sign up to set email alerts
|

A Signature in the Current during Early Events in the Pitting Corrosion of Aluminum

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…The reader will note that the fundamental event in passivity breakdown, according to the PDM, is the formation of a cation vacancy condensate at the m/bl interface. The formation of such blisters as the precursors to passivity breakdown on aluminum has been detected and described by Bargeron and Givens and by McCafferty et al, amongst others [68,69,70,71,72,73,74]. Indeed, the present findings are entirely in concert with that previous work and provide an analytical basis for the vacancy condensation mechanism for passivity breakdown.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The reader will note that the fundamental event in passivity breakdown, according to the PDM, is the formation of a cation vacancy condensate at the m/bl interface. The formation of such blisters as the precursors to passivity breakdown on aluminum has been detected and described by Bargeron and Givens and by McCafferty et al, amongst others [68,69,70,71,72,73,74]. Indeed, the present findings are entirely in concert with that previous work and provide an analytical basis for the vacancy condensation mechanism for passivity breakdown.…”
Section: Discussionsupporting
confidence: 88%
“…At that point (potential, E c ), vacancy condensation occurs and continues around the periphery of the blister. The initial condensation point may be nanoscopic, but the radius of the blister increases with the square root of time and quickly grows to a micron size, as observed by Bargeron and Givens and others [68,69,70,71,72,73,74], with the size being determined by the rate of dissolution and the mechanical integrity of the cap. Thus, at some point during this expansion, the blister (remnants of the dissolving barrier layer) fractures and allows the electrolyte to penetrate into the blister, resulting in the emission of gas (H 2 , H 2 S, NH 3 and CH 4 , corresponding to oxide, sulfide, nitride, and carbide precipitates, respectively), as reported by Bargeron and Givens) [69,70,71].…”
Section: Discussionmentioning
confidence: 81%
“…17,18 Other workers have shown that under potentiostatic control the current from single active pits often shows rapid multiple transient events. [19][20][21] Bargeron and Givens observed very high frequency current events up to 4000 Hz and suggested they were caused by the oxide layer separating from the metal substrate. 19 Lillard found multiple events with Be occurring at about 1 Hz for a ͑0001͒ orientation.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Bargeron and Givens observed very high frequency current events up to 4000 Hz and suggested they were caused by the oxide layer separating from the metal substrate. 19 Lillard found multiple events with Be occurring at about 1 Hz for a ͑0001͒ orientation. He attributes the localization of these events to properties of the repassivation layer or development of a local solution chemistry which produces a memory of where the previous events took place.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this capacitance drop does not lie in the dielectric behaviour, but can be evaluated from the equivalent series circuit suggested e.g. in Reference [1,3] as a capacitance dissipation effect of the MnO 2 electrolyte and circuit inductance. The relation between the maximum DF and the capacitance cut-off frequency is valid in this case also.…”
Section: Real Capacitor ε /Capacitance and Df Frequency Dependencesmentioning
confidence: 99%